Potensi Kecurangan Non-Fungible Token: Dalam Lensa Akuntansi Forensik dan Syariah - Khomsatun, Siti (Accounting Department UNUSIA, 2024)
This study analyzes the possibility of fraud in Non-Fungible Tokens (NFT) transactions using forensic accounting and Sharia perspectives. This study employs a qualitative research method with in-depth and exploratory approach. Primary data were collected through interviews with NFTs Creators, Auditors, and DSN-MUI Member, while the secondary data were from article journals, scientific books, theses, and websites. This study concludes that NFT has the potential for fraud, such as Pump-and-Dump, Rug Pull, and Money Laundering schemes, based on the nature of NFT itself. However, all of these fraud schemes can be prevented by the users (investors) who must be informed about what they are buying, either through educating themselves on fundamental analysis or by using forensic accounting techniques. From sharia perspective, NFT transactions are not permitted (haram) because they are lack of underlying assets and contain gharar (obscurity), dharar (danger), maysir (speculation), and also have been given a haram fatwa by the MUI of Indonesia.